49.6k views
0 votes
See the attachment below for the question.

See the attachment below for the question.-example-1
User Askewchan
by
5.4k points

2 Answers

4 votes

Answer: Third option.

Explanation:

We need to remember that:


a^m=a^n\\\\m=n

In this case, given this expression:


4^x
=8^(( x- 1))

We need to descompose 4 and 8 into their prime factors:


4=2*2=2^2


8=2*2*2=2^3

Rewriting the expression:


2^(2x)
=2^(3(x - 1) )

Then:


2x = 3(x - 1)

Finally, applying Distributive property on the right side and solving for "x", we get:


2x=3x-3\\\\3=3x-2x\\\\x=3

User Florian Treml
by
5.1k points
3 votes

Answer:

The correct answer is third option

x = 3

Explanation:

It is given that,

4ˣ = 8⁽ˣ ⁻ ¹⁾

To find the value of x

4ˣ = (2²)ˣ

8⁽ˣ ⁻ ¹⁾ = (2³)⁽ˣ ⁻ ¹⁾

4ˣ = 8⁽ˣ ⁻ ¹⁾

(2²)ˣ = (2³)⁽ˣ ⁻ ¹⁾

2²ˣ = 2⁽³ˣ ⁻ ³⁾

2x = 3x - 3

3x - 2x = 3

x = 3

The correct answer is third option

x = 3

User Ritsaert Hornstra
by
5.0k points